Willingness to pay for suicide prevention in Japan. Issue 5 (27th May 2016) - Sueki, Hajime
ABSTRACT: The present study aimed to establish willingness to pay for suicide prevention among taxpayers in Japan. We conducted an internet-based questionnaire survey using a double-bounded dichotomous choice contingent valuation, and analyzed data for 956 participants. The median willingness to pay to reduce the mortality risk from suicide by 25% was JPY 1, 572 ($13.67 USD). Being married was significantly associated with willingness to pay. The willingness to pay to reduce the mortality risk from suicide may be lower than that to reduce other mortality risks such as traffic accidents.